2018
DOI: 10.1073/pnas.1811695115
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational hypocortisolism and behavioral disruption are induced by the antidepressant fluoxetine in male zebrafishDanio rerio

Abstract: The global prevalence of depression is high during childbearing. Due to the associated risks to the mother and baby, the selective serotonin reuptake inhibitor fluoxetine (FLX) is often the first line of treatment. Given that FLX readily crosses the placenta, a fetus may be susceptible to the disruptive effects of FLX during this highly plastic stage of development. Here, we demonstrate that a 6-day FLX exposure to a fetus-relevant concentration at a critical developmental stage suppresses cortisol levels in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 79 publications
11
67
0
Order By: Relevance
“…Serotonin, in this period, is considered an important regulator of motor neuron differentiation and locomotion in developing zebrafish [88,89], but whether developmental serotonin acts as a programmer of the endocrine stress axis in zebrafish has not been directly investigated. Irrespective of an involvement of developmental serotonin, a recent study [57] was first to show that developmental exposure to FLX (both exposed F 0 males and females) reduces F 0 baseline and mechanical stressor-induced whole-body cortisol levels, and that this phenotype can be transmitted in subsequent generations, especially in males. We here additionally determine that this developmental exposure to FLX in the F 0 generation results in maternal, but not paternal transmission of reduced basal cortisol to F 1 offspring generated from crosses of 5 months old, but not 9 months old F 0 zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin, in this period, is considered an important regulator of motor neuron differentiation and locomotion in developing zebrafish [88,89], but whether developmental serotonin acts as a programmer of the endocrine stress axis in zebrafish has not been directly investigated. Irrespective of an involvement of developmental serotonin, a recent study [57] was first to show that developmental exposure to FLX (both exposed F 0 males and females) reduces F 0 baseline and mechanical stressor-induced whole-body cortisol levels, and that this phenotype can be transmitted in subsequent generations, especially in males. We here additionally determine that this developmental exposure to FLX in the F 0 generation results in maternal, but not paternal transmission of reduced basal cortisol to F 1 offspring generated from crosses of 5 months old, but not 9 months old F 0 zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…In both fish [20,3638] and mammals [39,40] endocrine disrupting effects of FLX have been reported at and below human therapeutic plasma (equivalent) concentrations, which include the endocrine stress axis function [4146]. While developmental [4753] and adult [16,20,46,5456] consequences of FLX exposure have been comparatively well studied in fish at different levels of biological organization [15], intergenerational effects of developmental FLX exposure have only recently been described in zebrafish [57]. This study revealed that developmental FLX exposure has the capacity to differentially reduce basal cortisol concentrations or blunt mechanical stressor induced cortisol concentrations in subsequent generations.…”
Section: Introductionmentioning
confidence: 99%
“…Male zebrafish were randomly allocated to sham-treated and metyrapone-exposed groups that were held in static tanks (6 fish per tank). After an overnight acclimation period, the water in metyrapone-exposed tanks was replaced with 325.4 µmol l −1 metyrapone in system water (Vera-Chang et al, 2018). Water changes were carried out every 24 h and all tanks were covered to reduce degradation of metyrapone by light exposure.…”
Section: Series 3: Effect Of Inhibiting Cortisol Synthesis On Forebramentioning
confidence: 99%
“…In the last decade, a growing scientific interest on transgenerational epigenetic inheritance has emerged [69][70][71]. However, despite the increasing number of studies showing transgenerational epigenetic impacts, the integration of epigenetic markers in the frame of hazard and risk assessment is still not a reality.…”
Section: Discussionmentioning
confidence: 99%